2023
DOI: 10.1038/s41598-023-30018-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between egg consumption and metabolic health status in overweight and obese adolescents

Abstract: Existing evidence examining the relation between egg consumption and metabolic health of overweight/obese adolescents is scarce. We examined the association between egg consumption and metabolic status in Iranian overweight/obese adolescents. Using multistage cluster random sampling approach, overweight/obese adolescents (n = 203) with ages from 12 to 18 years old were selected for the present cross-sectional study. A validated 147-item food frequency questionnaire was adopted to determine usual dietary intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…They contain protease inhibitors, nutrients and functional lipids, which highlights the importance of its consumption for human health, as well as disease prevention and treatment [44]. Higher egg consumption was negatively associated with a reduced chance of being metabolically unhealthy obese (muo) in overweight/obese adolescents, especially in boys and overweight individuals [45]. in addition, the use of satiety-inducing foods, such as eggs, can improve adherence to a calorie-restricted diet in children and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They contain protease inhibitors, nutrients and functional lipids, which highlights the importance of its consumption for human health, as well as disease prevention and treatment [44]. Higher egg consumption was negatively associated with a reduced chance of being metabolically unhealthy obese (muo) in overweight/obese adolescents, especially in boys and overweight individuals [45]. in addition, the use of satiety-inducing foods, such as eggs, can improve adherence to a calorie-restricted diet in children and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, reductions of body weight following dried whole egg intake has also been observed in diabetic and diet-induced obesity rat models [63,64]. Population-based and observational studies have also reported conflicting sex-specific differences in the effects of egg intake on body composition, with consumption of >50 g egg/day being associated with reduced risk of central obesity and body fat in females only in a study of 2241 Chinese adults (age 18-80 y) [65], whereas stronger protective associations between egg intake and reduced risk of being classified as metabolically unhealthily obese were observed in males [66]. In contrast, Shim and Seo [27] observed that an intake of 2-3 eggs/week and 4-6 eggs/week based on food frequency questionnaire responses were associated with higher body fat mass in males and females, respectively, in 13,366 adults from the Korea National Health and Nutrition Examination Surveys 2008-2011.…”
Section: Discussionmentioning
confidence: 99%
“…Perbedaan harga ini merupakan peluang bagi peternak ayam petelur untuk meningkatkan pendapatan usahanya. Omega-3 pada telur dapat dihasilkan melalui manipulasi pakan dengan memasukkan suplemen omega-3 pada pakan ayam (National Institute of Health, 2017) (Tabatabaeyan et al, 2023). Penggunaan suplemen omega-3 sebanyak 5% dalam pakan ayam ras petelur dilaporkan dapat meningkatkan kandungan DHA (docosa hexanoat) 10 kali lipat dan menurunkan kadar kolesterol LDL (low density lipoprotein) sebanyak 50%.…”
Section: Pendahuluanunclassified